Analisis Jenis Kerusakan Perkerasan Lentur (Flexible Pavement) Pada Ruas Jalan Raya Pasar Kemis. Kecamatan Pasar Kemis. Kabupaten Tangerang Banten - Fadillah, Muhammad; Khamaludin, Khamaludin; Abdillah, Hafiz (Universitas Islam Syekh Yusuf Tangerang, 2024)
The road is intended for general traffic. Basically, the implementation of public roads is required to ensure that roads can be used as much as possible for the prosperity of the people, especially to increase national economic growth, for example on the Pasar Kemis highway, Tangerang Regency with a length of 4.86 km. As for some of the damage factors on the highway, namely: cracks, aggregate thirst, holes, and waves with varying degrees of damage for the most dominant, namely the level of damage there are 3 types of damage such as waves 53.7%, holes 48.3% and loose aggregate 30 ,6% of the calculation and summation. The purpose of this study was to determine the types of road damage on flexible pavement, the factors causing damage to traffic volume loads, rainfall and drainage systems to the value of damage to highways. In this study using quantitative methods and qualitative methods where numerical data from observations and calculations in the field will be analyzed by statistical methods.